2017
DOI: 10.1007/s10654-017-0345-9
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette and waterpipe use in two adolescent cohorts: cross-sectional and longitudinal associations with conventional cigarette smoking

Abstract: Alternative tobacco products are increasing in popularity. An important question is whether their use is associated with or even leads to conventional smoking, but large-scale (European) studies are scarce. In two cohorts of Dutch adolescents (Cohort I n = 6819, mean age = 13.8 SD = 1.1, 48.2% female; Cohort II n = 2758, mean age = 17.3 SD = 1.8, 61.3% female), we investigated use of electronic (e)-cigarettes with nicotine, e-cigarettes without nicotine and waterpipe. Generalized estimating equation modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 30 publications
0
90
0
3
Order By: Relevance
“…Mounting evidence supports this view [2,[6][7][8] and that vaping may aid smoking cessation [2,[9][10][11]. Nevertheless, concerns remain [3,12], particularly around risks of vaping introducing youth to nicotine and cigarette use [13][14][15][16], though so far regular (at least weekly) vaping by youth in the UK has been rare [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence supports this view [2,[6][7][8] and that vaping may aid smoking cessation [2,[9][10][11]. Nevertheless, concerns remain [3,12], particularly around risks of vaping introducing youth to nicotine and cigarette use [13][14][15][16], though so far regular (at least weekly) vaping by youth in the UK has been rare [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The level of nicotine in the e-liquid has been shown to impact nicotine delivery, [38][39][40] and previous studies have reported that level of nicotine in e-cigarette e-liquid was associated with frequency of e-cigarette use, cigarette use, and likelihood of cigarette initiation. 17,24 However, no previous studies examining this association have accounted for the type of device used. It is possible that use of e-liquids with nicotine was not associated with number of cigarettes smoked because the type of device was a better predictor of effective nicotine dose than whether participants reported using nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…To help guide regulatory strategies, data are urgently needed on factors that differentiate the risk of transition from e-cigarettes to heavier patterns of combustible cigarette use. The use of e-cigarettes with a higher nicotine level has been associated with an increased likelihood of combustible cigarette initiation 17,24 and both greater frequency of cigarette use in the past month and more cigarettes smoked per day at follow-up. 24 Other product characteristics that are amenable to regulation may also promote or discourage the transition to combustible tobacco use but have not yet been thoroughly investigated.…”
mentioning
confidence: 99%
“…Thus, there is limited information in this sense. One study from Netherlands stated that e-cigarettes without nicotine are more used for e-cigarette experimentation (Treur, Rozema, Mathijssen, van Oers, & Vink, 2018) (Table 1).…”
Section: Prevalence Of E-cigarettes Usementioning
confidence: 99%